Over-expression of the Pikh gene with a CaMV 35S promoter leads to improved blast disease (Magnaporthe oryzae) tolerance in rice - Azizi, Parisa; Yusop, Mohd Rafii; Abdullah, Siti Nor Akmar; Musa, Mohamed Hanafi; Mahmood, Maziah; Sahebi, Mahbod; Ashkani, Sadegh; Taheri, Sima; Jahromi, Mohammad Faseleh (Frontiers Media, 2016)
Magnaporthe oryzae is a rice blast fungus and plant pathogen that causes a serious rice disease and, therefore, poses a threat to the world’s second most important food security crop. Plant transformation technology has become an adaptable system for cultivar improvement and to functionally analyze genes in plants. The objective of this study was to determine the effects (through over-expressing and using the CaMV 35S promoter) of Pikh on MR219 resistance because it is a rice variety that is susceptible to the blast fungus pathotype P7.2. Thus, a full DNA and coding DNA sequence (CDS) of the Pikh gene, 3172 bp, and 1206 bp in length, were obtained through amplifying the gDNA and cDNA template from a PH9-resistant rice variety using a specific primer. Agrobacterium-mediated transformation technology was also used to introduce the Pikh gene into the MR219 callus. Subsequently, transgenic plants were evaluated from the DNA to protein stages using polymerase chain reaction (PCR), semi-quantitative RT-PCR, real-time quantitative PCR and high performance liquid chromatography (HPLC). Transgenic plants were also compared with a control using a real-time quantification technique (to quantify the pathogen population), and transgenic and control plants were challenged with the local most virulent M. oryzae pathotype, P7.2. Based on the results, the Pikh gene encodes a hydrophilic protein with 18 sheets, 4 helixes, and 21 coils. This protein contains 401 amino acids, among which the amino acid sequence from 1 to 376 is a non-cytoplasmic region, that from 377 to 397 is a transmembrane region, and that from 398 to 401 is a cytoplasmic region with no identified disordered regions. The Pikh gene was up-regulated in the transgenic plants compared with the control plants. The quantity of the amino acid leucine in the transgenic rice plants increased significantly from 17.131 in the wild-type to 47.865 mg g-1 in transgenic plants. The M. oryzae population was constant at 31, 48, and 72 h after inoculation in transgenic plants, while it was increased in the inoculated control plants. This study successfully clarified that over-expression of the Pikh gene in transgenic plants can improve their blast resistance against the M. oryzae pathotype P7.2.